Moral Value and Character Building Tugu Silalahi Batak Toba Folklore into Teaching Materials English Subject - Teodora Manjorang; Yenita Br Sembiring; Mawyda Sitanggang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this research is to develop and build values and moral character for the next generation, especially for high schools, through the folklore of the Tugu Silalahi Batak Toba. This research approach was carried out using qualitative descriptive. Teaching moral values and character building from the Toba Batak Silalahi folklore will be applied by learning English on narrative text material and can also be in descriptive text. In the story, the moral values are mutual love, being fair, honest, obedient, socially caring, humble. The character building in this story is a responsibility, hard work, courage, decisiveness, cleverness, patience, and keeping promises. Keywords: Character Building, Folklore, Moral Values, Teaching Materials